Group Dynamics of Livestock based Self Help Groups (SHGs) - Chadda, Akshita; Jadoun, Y.S.; Kansal, S.K.; Singh, Jaswinder; Deshmukh , Bharti (Indian Journal of Extension Education, 2019)
The study was conducted in Ludhiana district of Punjab to observe the group dynamics of beneficiaries of livestock based Self Help Groups (SHGs) formed by different Self Help Group Promoting Institutions (SHGPIs). A total 120 SHG beneficiaries i.e., 40 beneficiaries from each SHGPIs were subjected to structured interview schedule. Majority (91.67%) of the beneficiaries were involved solely in dairy farming practices. Homogeneity in standard of living was one of the major factors promoting SHG formation as stated by 87.50 per cent NGO promoted SHG beneficiaries and 75.00 per cent Government promoted SHG beneficiaries. Majority of the beneficiaries believed that they joined the group for ‘family welfare & economic independence’. Decision making power, self confidence of the beneficiaries was reported improved after joining SHGs. Only 09.17 per cent of the beneficiaries had attended training regarding animal husbandry practices. The main objective of group meetings was reported as ‘collecting savings’ and ‘inter-loaning among group beneficiaries’ as key purpose for utilizing saving amount. Milk sale and savings were the major income generating activities among all the beneficiaries. The difference between group dynamics was found statistically significant among the beneficiaries of different SHGPIs (P
Keywords: Group dynamics; Self help groups; Skill development; SHGPIs